Correlation Between Frailty and Perioperative Outcomes - Rodrigues, Diana; Almeida, Manuel Teixeira; Barbosa, Joselina; Mourão, Joana (Journal of the Portuguese Society of Anesthesiology, 2019)
Introduction: Aging of the population is associated with an increase of people with frailty proposed for elective surgery, which implies an adequate perioperative management of these patients. The goal of this study was to verify the existence of a correlation between frailty and postoperative outcomes, including hospitalization length, hospital readmission, reoperation rate, postoperative complications and mortality. Material and Methods: We performed an observational prospective study including 100 patients proposed for elective surgery in a University Hospital. Frailty was defined as a score ≥ 6 on the Tilburg Frailty Indicator scale, in the portuguese validated version. Student's t-test and Fisher's exact test were used for comparison. Results: The prevalence of frailty in our study was 69%. There was an association between frailty and higher age (p = 0.02), female gender (p= 0.032), and higher ASA-PS score (p = 0.013). Patients with frailty had longer hospitalizations (p = 0.007) and a higher hospital readmission rate (p = 0.028). We did not find differences in the variables surgical risk, type of anaesthesia, duration of surgery, Charlson Comorbidity Index, Lee Revised Cardiac Risk Index, presence of complications and mortality. Discussion: The prevalence of frailty was higher than that described in the literature, possibly because we included only patients proposed for surgery. The main limitation of the study is patients' heterogeneity regarding the surgery performed. Conclusion: In this study, we found an association between frailty and a longer duration of hospitalization and hospital readmission rate. Frailty demonstrated to be a good predictor of perioperative morbidity.